Animal dietary exposure: overview of current approaches used at EFSA. (15th November 2019) - ; Ardizzone, Michele; Binaglia, Marco; Cottrill, Bruce; Cugier, Jean‐Pierre; Ferreira, Lucien; Gómez Ruiz, Jose Ángel; Innocenti, Matteo; Ioannidou, Sofia; López Puente, Secundino; Merten, Caroline; Nikolic, Marina; et al.
Abstract: At EFSA, animal dietary exposure estimates are undertaken by several Panels/Units to assess the risk of feed contaminants, pesticide residues, genetically modified feed and feed additives. Guidance documents describing methodologies for animal dietary exposure assessment are available both at EFSA and international levels. Although appropriate within pertinent regulatory frameworks, the methodologies used to assess animal dietary exposure vary across risk assessment areas. There are different approaches ranging from quick worst‐case estimations to more refined methods assessing actual exposure, resulting from the use of a heterogeneous selection of animal populations and default values to estimate feed intake. Furthermore, current feed classification systems in place at international and national levels contain a large and heterogeneous number of feed materials, which may benefit from further harmonisation efforts. This technical report presents an overview of the current approaches in place at EFSA to assess the exposure to chemicals in feed. The possibility for a greater harmonisation of feed classification and terminology is also addressed by comparing the structure of the EU catalogue of feed materials and the Harmonised OECD tables of feedstuffs derived from field crops with the EFSA FoodEx2 system.